Question

    The expansion of (3a - 4b - 2c)² is:

    A 9a² + 16b² + 4c² - 24ab + 8bc + 12ac Correct Answer Incorrect Answer
    B 9a² + 16b² + 4c²+ 12ab - 8bc + 6ac Correct Answer Incorrect Answer
    C 9a² + 16b² + 4c² - 24ab - 12ac + 16bc Correct Answer Incorrect Answer
    D 9a² + 16b² + 4c² - 24ab + 16bc - 6ac Correct Answer Incorrect Answer

    Solution

    ATQ, Expand (3a - 4b - 2c)²   using the formula: On Squaring each term: (3a)2 = 9a2,  (− 4b)2 =16b2,   (−2c)2 = 4c2 Multiply pairs of terms: 2(3a) (−4b) = −24ab,  2(3a) (−2c) = −12ac,  2(−4b) (−2c) = 16bc On Combining everything, we get 9a ²  + 16b²  + 4c²  – 24ab – 12ac + 16bc

    Practice Next

    Relevant for Exams: